Pemberdayaan UMKM ‘ Permata Batik ‘ Di Kalurahan Bimomartani Kapanewon Ngemplak Kabupaten Sleman - Zulianti, Tutik Wahyuningsih (Jurnal Masyarakat dan Desa, 2022)
The Permata Batik MSMEs is a leading MSME in Bimomartani Village, Ngemplak, Sleman. that has been able to empower and prosper the local community. This research aims to find out the empowerment that has been done towards Permata Batik MSMEs, the driving and inhibiting factors in this empowerment. The type of this research is qualitative. Informants came from the Permata Batik MSMEs, the community and the Village Government. The data collection techniques with observation, interview and documentation. The analysis technique is descriptive. The results of the study showed that empowerment began with the awareness and belief of the members of MSME that batik is typicalal handicraft of Indonesian society and Javanese in particular. The existence of an economic crisis, the batik business became the foundation of MSME actors. The driving factor is a strong understanding of Yogyakarta as the world's entry point to recognize and love batik crafts. The inhibiting factors are the weak knowledge and skills of MSME actors, lack of product innovation, and capital problems. Conclusion, the empowerment of Permata Batik MSMEs has been running well by recruiting labor from the residents of Bimomartani Village. Marketing has expanded to the international market. However, there are still several obstacles that must be overcome, so that the sustainability of the Permata Batik MSMEs business can remain a source of income and community welfare